Cotidianidad y cuidado de las mujeres que presentan pre-eclampsia - Torres Lagunas, María De Los Ángeles (2013)
We present results that emerged from the qualitative, descriptive, exploratory, research study, which aimed to describe and analyze the life of women with pre-eclampsia in a semi-urban community of Chimalhuacan in the State of Mexico. This disease is a public health problem in Mexico, ranked first in maternal deaths over two decades Oats J, Joerin V, Dozdor L, and Bres S (2007, p. 94)and occurs in 5 to 10 % of all pregnancies (Villanueva, 2010 ). Maffesoli, Morin, Maturana, Varela, Figueiredo and Boff are the authors who gave the theoretical support to the results. Depth interviews were conducted with sixteen women, during pregnancy. The data analysis was performed considering the principles of Orlandi (Orlandi, 2002). This analysis revealed two categories: Self-eco-socio-organization of everyday life of women with preeclampsia and creating life in the everyday. The first category consists of three sub-categories: "time, space and movement", "identity" and "solidarity" and the second category consists of two subcategories: "corporeality-subjectivity" and "reversal of health". The final considerations emphasized that self-eco-socio-organization and create life from the perspective of complex thinking includes understanding holistically the internal logic of women as living beings, organized and systemic; and the external logic of context and daily life environment of these women, which is not always positive by the presence of emergent events such as preeclampsia that disrupts corporeality-subjectivity and life of the pregnant woman making her coexist with crisis situations that occur through recursive phenomena of self-eco-socio- organization and autopoiesis. These findings are important to build singular, sensitive and culturally specific models in care of women with this disease.